The Effect of Other Comprehensive Income, Leverage, and Profitability on Profit Management in LQ45 Index Companies Listed on the Indonesia Stock Exchange for the 2020-2023 Period - Juliantari, Ni Luh Manik; Adnantara, Komang Fridagustina; Adi, I Ketut Yudana (LPPPIPublishing, 2025)
The main objective of this study is to analyze the effect of other comprehensive income, leverage and profitability on earnings management in LQ45 index companies listed on the IDX for the 2020-2023 period. The research method used is quantitative, with a sample of 96 companies. The results of the study indicate that other comprehensive income and leverage do not have a partial effect on earnings management. While profitability has a positive effect on earnings management. This shows that the higher the profitability, the higher the level of opportunity for managers to practice earnings management. The variables other comprehensive income, leverage and profitability simultaneously affect earnings management.